Appalachia in the classroom : teaching the region - Burriss, Theresa L.; Gantt, Patricia M., 1943- (Ohio University Press series in race, ethnicity, and gender in Appalachia., 2013)
This book contributes to the twenty-first century dialogue about Appalachia by offering topics and teaching strategies that represent the diversity found within the region. Appalachia is a distinctive region with various cultural characteristics that can't be essentialized or summed up by a single text. The book offers chapters on teaching Appalachian poetry and fiction as well as discussions of nonfiction, films, and folklore. Educators will find teaching strategies that they can readily implement in their own classrooms.